Neferine Attenuates Acute Kidney Injury by Inhibiting NF-κB Signaling and Upregulating Klotho Expression - Li, Huihui; Chen, Wenhang; Chen, Yusa; Zhou, Qiaoling; Xiao, Ping; Tang, Rong; Xue, Jing (Frontiers in Pharmacology, 2019)
Purpose: Acute kidney injury (AKI) is associated with high morbidity and mortality, and no effective drug is available. We explored whether neferine, a bisbenzylisoquinoline alkaloid, attenuated AKI, and the possible mechanisms in play in vivo. Methods: We induced AKI using ischemia-reperfusion (I/R) and lipopolysaccharide (LPS). C57 BL/6 male mice were randomized into two groups each containing four subgroups: Control, neferine, I/R or LPS, and I/R or LPS + neferine. Mice were sacrificed 24 h after AKI induction and kidneys and sera were collected. Results: Neferine significantly alleviated kidney functional loss and pathological damage. Compared to the model group, neferine prevented kidney apoptosis, suppressed inflammatory cytokine production, and inhibited nuclear translocation of NF-κB; it also restored Klotho expression. Conclusion: Neferine mitigated renal injury in AKI models, perhaps by suppressing NF-κB activation and increasing Klotho expression.